PENGUJIAN PECKING ORDER THEORY PADA EMITEN SYARIAH DI BURSA EFEK JAKARTA - Sutapa Sutapa; Hendri Setyawan; Heri Laksito (University of Merdeka Malang, 2008)
The objective of this study was to test empirically whether capital structure decisionof Indonesian firms followed a hierarchy of sources of finance called Pecking Order. Samplesin this study were 29 firms listed in Jakarta Islamic Index (JII) from 2001 to 2004. Variabelsused as proxy of Pecking Order Theory (POT) were profitability, investment opportunity andfirm size. The results of this study were as follows: a). simultaneously, all proxies for POT couldexplain capital structure at Indonesian Capital Market, b). more profitable firms were lesslevered, c). bigger firms were more levered, d). result for investment opportunity did notsupport hypothesis. Firms listed at JII tended to follow POT in their financing decision. Part ofresults of this study was consistent with study of Wiwattanakantang (1999), Fama and French(2002), Benito (2003) and Mutamimah (2003).